Food safety practice and its associated factors among household food handlers in Patuakhali, Bangladesh: A cross-sectional study - M. M. Mehedi Hasan; Nayeem Rahman; Md. Mofidul Islam; H. M. Sabbir Ahmed; Shuvajit Mondal; Farzana Afroz; Mohammad Abdulla Al Noman (PLoS ONE, 2025)
Food safety practices play a crucial role in the prevention of foodborne diseases, particularly in low- and middle-income countries like Bangladesh. This study assessed food safety practices among household food handlers in Patuakhali, Bangladesh, and identified associated factors influencing these practices. A cross-sectional study was conducted among 300 randomly selected households, using structured interviews and direct observations. The findings revealed that only 46% of participants demonstrated good food safety practices, with notable deficiencies in proper handwashing techniques (36.7%). Multiple logistic regression analysis identified that secondary education (AOR = 2.84; 95% CI: 1.44, 5.59), government employment (AOR = 5.74; 95% CI: 1.24, 26.53), monthly income between 15,000 and 30,000 BDT (AOR = 4.50; 95% CI: 2.17, 9.31), and participation in food safety training (AOR = 5.01; 95% CI: 1.95, 12.90) were significantly associated with good food safety practices. Conversely, living in rural areas (AOR = 0.30; 95% CI: 0.13–0.67) and, being aged 39–58 years (AOR = 0.36; 95% CI: 0.15–0.84) were associated with poor food safety practices. Addressing these factors, particularly socioeconomic disparities and offering targeted food safety education, could significantly improve public health outcomes and overall food safety practices.